2016
DOI: 10.2220/biomedres.37.29
|View full text |Cite
|
Sign up to set email alerts
|

<b>PCR-dipstick DNA chromatography for profiling of a subgroup of cariesassociated bacterial species in plaque from healthy coronal surfaces and periodontal </b><b>pockets </b>

Abstract: The onset of plaque-mediated disease, including dental caries and periodontal diseases, is highly associated with compositional change of the resident microflora from the ecological perspective. As specific bacterial profiles have been linked to different disease stages, microbial compositional measurements might therefore have great value for clinical diagnosis. Previously we have reported a dry-reagent strip biosensor-PCR-dipstick DNA chromatography, which utilized molecular recognition of oligonucleotides a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
8
0
1
Order By: Relevance
“…Early studies suggest that that the main carbon metabolic pathways, such as the Embden-Meyerhof-Parnas (EMP) pathway, the pentose phosphate (PP) pathway, and the tri-carbonic acid (TCA) cycle, as well as amino acid metabolism-related pathways, are in operation in the oral biofilm in vivo and exhibit similar characteristics to those of Streptococcus and Actinomyces [ 81 , 82 ]. Dysregulation of these main carbon metabolic pathways have been correlated to dental caries, periodontal disease and oral cancer in small studies [ 83 85 ]. The following five saliva metabolomic biomarkers can discriminate from early HNSCC patients from controls: propionylcholine, N-Acetyl-L-phenylalanine, sphinganine, phytosphingosine, and S-carboxymethyl-L-cysteine [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Early studies suggest that that the main carbon metabolic pathways, such as the Embden-Meyerhof-Parnas (EMP) pathway, the pentose phosphate (PP) pathway, and the tri-carbonic acid (TCA) cycle, as well as amino acid metabolism-related pathways, are in operation in the oral biofilm in vivo and exhibit similar characteristics to those of Streptococcus and Actinomyces [ 81 , 82 ]. Dysregulation of these main carbon metabolic pathways have been correlated to dental caries, periodontal disease and oral cancer in small studies [ 83 85 ]. The following five saliva metabolomic biomarkers can discriminate from early HNSCC patients from controls: propionylcholine, N-Acetyl-L-phenylalanine, sphinganine, phytosphingosine, and S-carboxymethyl-L-cysteine [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…After the PCR or loop-mediated isothermal amplification (LAMP), the C-PAS is dipped into the reaction mixture. The amplification products immobilized with single-tag hybridization are then visually detected with a streptavidin–biotin interaction using a streptavidin-coated blue-colored latex microsphere. It was revealed that the STH C-PAS system is available for US sequence detection. The LODs determined for each GM event are listed in Table , and the representative results obtained from GM soybeans are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Oligonucleotides corresponding to five different bacteria were immobilized at different lines on a paper strip, and due to the attachment of blue latex microspheres to the PCR amplicons, the corresponding test lines became visibly blue after dipping the strip into bacteria‐containing samples (Tian et al., 2014). In 2016, the research group compared the results of their method between the previous healthy individuals and patients with periodontitis, demonstrating reduced microbial diversity in diseased patients as well as differentiation between health‐associated and disease‐associated bacteria (Tian et al., 2016). Methods such as this show the promise for biosensors to be clinically translated for microbiome analysis at the bedside.…”
Section: Moving Microbiome Analysis From the Laboratory To The Clinicmentioning
confidence: 99%